2023
DOI: 10.3389/fphar.2023.1103062
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and necroptosis in cisplatin-induced acute kidney injury: Recent advances regarding their role and therapeutic potential

Abstract: Cisplatin (CP) is a broad-spectrum antineoplastic agent, used to treat many different types of malignancies due to its high efficacy and low cost. However, its use is largely limited by acute kidney injury (AKI), which, if left untreated, may progress to cause irreversible chronic renal dysfunction. Despite substantial research, the exact mechanisms of CP-induced AKI are still so far unclear and effective therapies are lacking and desperately needed. In recent years, necroptosis, a novel subtype of regulated n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 274 publications
0
9
0
Order By: Relevance
“…Technically, more extensive control data such as CASPASE3 assessment in Becn1 +/− mice would be desirable. Furthermore, previous studies showed that other pathways of cell death such as necroptosis and ferroptosis play an important role in cisplatin nephropathy and these pathways were not in the scope of our study [ 60 , 61 , 62 , 63 ]. Also, inflammatory pathways with various mediators including tumor necrosis factor alpha (TNFα), toll-like receptor (TLR) signaling and chemokine (C-X-C motif) ligand (CXCL) 16 and the CXCL1-CXCR 2 axis have been shown to contribute to renal deterioration in cisplatin nephropathy [ 54 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 90%
“…Technically, more extensive control data such as CASPASE3 assessment in Becn1 +/− mice would be desirable. Furthermore, previous studies showed that other pathways of cell death such as necroptosis and ferroptosis play an important role in cisplatin nephropathy and these pathways were not in the scope of our study [ 60 , 61 , 62 , 63 ]. Also, inflammatory pathways with various mediators including tumor necrosis factor alpha (TNFα), toll-like receptor (TLR) signaling and chemokine (C-X-C motif) ligand (CXCL) 16 and the CXCL1-CXCR 2 axis have been shown to contribute to renal deterioration in cisplatin nephropathy [ 54 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 90%
“…Meanwhile, ATG5 is recruited and helps activate the closure of the autophagosomes [ 27 ]. It was also stated that the cisplatin injection was associated with suppressing autophagic LC3II expression [ 28 ], and the more autophagy got inhibited, the worse kidney function got [ 26 , 29 , 30 ]. In the current study, mice treated with cisplatin showed substantial repression in the gene expression of Beclin 1, ATG5, as well as inhibition of LC3-II gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental investigations have remarkably illuminated promising strategies for enhancing AKI prognosis through the modulation of mitochondrial function. Notably, instances of AKI induced by both ischemia and cisplatin showcased significant amelioration when apoptosis was strategically inhibited through the ablation of Bax and Bak [105,106]. This groundbreaking revelation highlights the intricate connection between mitochondrial dynamics and the apoptotic cascade, shedding light on potential therapeutic targets for preventing AKI progression.…”
Section: Mitochondrial Modulation In Aki: a Pathway To Prognostic Imp...mentioning
confidence: 96%
“…Mitochondria are also central to the initiation of AKI, potentially paving the way for the transition to CKD following exposure to nephrotoxic agents [108]. Maleic acid (MA)induced AKI, notably affecting renal proximal tubules, is associated with mitochondrial dysfunction [105,106]. MA-induced kidney injuries impact renal ammoniagenesis and mitochondrial energy homeostasis and induce mitochondrial permeability transition pore opening, leading to cell apoptosis [109][110][111].…”
Section: Mitochondrial Modulation In Aki: a Pathway To Prognostic Imp...mentioning
confidence: 99%